Sayang semakin matang = A Singaporean coming of age ceremony - Teo, Felicia Jing Hui (Nanyang Technological University, 2021)
Sayang Semakin Matang ( Sayang Matang for short ) explores the alternative history in which every 12-year-old Singaporean undergoes a coming-of-age ceremony. Five fictional artifacts each tell the story of the rite behind it.